El pensamiento rizomático en la construcción de un modelo didáctico que vivencie la formación integral en el esquema de Educación Virtual de la Universidad Santo Tomás de Aquino de Bucaramanga (2012)
Lot of ideas has been produced regarding the concepts of e-learning and holistic training. However, few of them establish a relation between both discourses in order to find new challenges pedagogy faces in this new technological age. The growing technological advances bring new ways of conceiving education. E-learning seems to privilege the development of cognitive competencies. In the first part of the article, it is made a historical review on the way technology has set new challenges to education from the invention of the first printing machine until the apparition of Internet and the digital age. Then the different produced discourses on the field of e-learning and holistic training are analyzed by applying the Archeology of Knowledge proposed by Michel Foucault. After this, the author shows the way Holistic training is evidenced in the learning routes that are part of the virtual rooms. Afterwards, the idea of Holistic training is connected to the proposal of rizomatic thinking by Gilles Deleuze. Finally, new sights for the Thomas de Aquinas pedagogical model with regards to the e-learning are shown, through some problematic questions.